Nurses' labour supply elasticities: The importance of accounting for extensive margins - Barbara Hanel; Guyonne Kalb; Anthony Scott (Institute for the Study of Labor (IZA), 2012)
Many countries face a continuing shortage in nurses' labour supply. Previous research suggests that nurses respond only weakly to changes in wages. We estimate a multi-sector model of nursing qualification holders' labour supply in different occupations. A structural approach allows us to model the labour force participation decision, the occupational and shift-type choice, and the decision about hours worked as a joint outcome following from maximizing a utility function. Disutility from work is allowed to vary by occupation and also by shift type in the utility function. Furthermore, we allow the preference parameters in the utility function to vary by certain family characteristics and personality. Our results suggest that average wage elasticities might be higher than previous research has found. This is mainly due to the effect of wages on the decision to enter or exit the profession, which was not included in the previous literature, rather than from its effect on increased working hours for those who already work in the profession. We find that the negative labour supply elasticities with respect to income are higher for nurses with children, while the positive elasticities with respect to wages are higher for low-qualified, older and childless nurses. Elasticities do not appear to vary by personality trait.
urn:nbn:de:101:1-201301213826
Keywords: J22; J24; I10; I11; 330; nursing; labour supply; shift work; wage elasticities; Pflegeberufe; Arbeitsangebot; Lohn; Preiselastizität; Schätzung; Australien